2021
DOI: 10.1186/s12890-021-01586-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound heterozygous mutations of DNAH5 identified in a pediatric patient with Kartagener syndrome: case report and literature review

Abstract: Background Kartagener syndrome is a subtype of primary ciliary dyskinesia that may exhibit various symptoms including neonatal respiratory distress and frequent infections of the lung, sinus and middle ear because of the impaired function of motile cilia. In addition to typical symptoms of primary ciliary dyskinesia, patients with Kartagener syndrome also show situs inversus. It is an autosomal recessive disorder which is mostly caused by mutations in DNAH5. Kartagener syndrome is often underdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our literature review revealed that the hearing loss was different depending on the gene involved ( Table 1 ). Variants in CCDC114 cause sensorineural hearing loss (SNHL) ( Li et al, 2019 ), while variants in CCN O, CDH3 , DNAH5 and OFD1 cause conductive hearing loss (CHL) ( Bukowy-Bieryllo et al, 2019 ; Fan et al, 2019 ; Henriques et al, 2021 ; Wang et al, 2021 ; Yang et al, 2022 ). In addition, the clinical findings were summarized to conclude the different symptoms, age at onset or diagnosis among PCD patients with CHL and SNHL ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review revealed that the hearing loss was different depending on the gene involved ( Table 1 ). Variants in CCDC114 cause sensorineural hearing loss (SNHL) ( Li et al, 2019 ), while variants in CCN O, CDH3 , DNAH5 and OFD1 cause conductive hearing loss (CHL) ( Bukowy-Bieryllo et al, 2019 ; Fan et al, 2019 ; Henriques et al, 2021 ; Wang et al, 2021 ; Yang et al, 2022 ). In addition, the clinical findings were summarized to conclude the different symptoms, age at onset or diagnosis among PCD patients with CHL and SNHL ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic testing is becoming more common and feasible in the diagnosis of KS due to recent advances in next-generation sequencing. DNAH5 is reportedly the most frequently mutated gene in patients with PCD [ 3 , 4 ]. It encodes the dynein axonemal heavy chain 5 protein, which is a component of the outer dynein arm (ODA).…”
Section: Discussionmentioning
confidence: 99%
“…At least 100 different pathogenic variants in the DNAH5 gene have been reported (Zariwala et al 1993 ; Hornef et al 2006 ; Emiralioğlu et al 2020 ; Wang et al 2021 ). However, the clinical significance of copy number variations (CNVs) in DNAH5 has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%